Raising Healthy Children: Family Fitness - Lisa D. Chan; Ashley Hamm; Shari Bresin; Karla P. Shelnutt (EDIS, 2020)
This 3-page document discusses the importance of regular exercise for children and adults and provides a list of fun activities. Written by Lisa D. Chan, Ashley Hamm, Shari Bresin, and Karla P. Shelnutt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised November 2020.